The Potential of Streptomyces as Biocontrol Agents against the Rice Blast Fungus, Magnaporthe oryzae (Pyricularia oryzae) - Law, Jodi Woan-Fei; Ser, Hooi-Leng; Khan, Tahir M.; Chuah, Lay-Hong; Pusparajah, Priyia; Chan, Kok-Gan; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2017)
Rice is a staple food source for more than three billion people worldwide. However, rice is vulnerable to diseases, the most destructive among them being rice blast, which is caused by the fungus Magnaporthe oryzae (anamorph Pyricularia oryzae). This fungus attacks rice plants at all stages of development, causing annual losses of approximately 10%-30% in various rice producing regions. Synthetic fungicides are often able to effectively control plant diseases, but some fungicides result in serious environmental and health problems. Therefore, there is growing interest in discovering and developing new, improved fungicides based on natural products as well as introducing alternative measures such as biocontrol agents to manage plant diseases. Streptomyces bacteria appear to be promising biocontrol agents against a wide range of phytopathogenic fungi, which is not surprising given their ability to produce various bioactive compounds. This review provides insight into the biocontrol potential of Streptomyces against the rice blast fungus, Magnaporthe oryzae. The ability of various Streptomyces spp. to act as biocontrol agents of rice blast disease has been studied by researchers under both laboratory and greenhouse/growth chamber conditions. Laboratory studies have shown that Streptomyces exhibit inhibitory activity against M. oryzae. In greenhouse studies, infected rice seedlings treated with Streptomyces resulted in up to 88.3% disease reduction of rice blast. Studies clearly show that Streptomyces spp. have the potential to be used as highly effective biocontrol agents against rice blast disease; however, the efficacy of any biocontrol agent may be affected by several factors including environmental conditions and methods of application. In order to fully exploit their potential, further studies on the isolation, formulation and application methods of Streptomyces along with field experiments are required to establish them as effective biocontrol agents.